PEMANFAATAN BUAH NIPAH DAN UMBI BIT PADA PEMBUATAN FRUIT LEATHER - Sari, Kamelia; Pato, Usman (Fakultas Pertanian Universitas Riau, 2022)
Fruit leather is a snack food made from thin sheets of fruit. Depending on the fruit used, it has a consistent and distinct flavor. The goal of this study was to find the best ratio of Nipah pulp and beetroot pulp for making Fruit leather. A completely randomized design (CRD) was used in this study, with four treatments and four replications. This study compared Nipah fruit pulp and beetroot pulp, specifically NB1 (85:15), NB2 (75:25), NB3 (65:35), and NB4 (55:45). Water, ash, pH, fiber, antioxidant activity, and sensory tests for color, taste, texture, and overall assessment were the parameters observed in this study. Data were statistically analyzed at a 5% level using Analysis of Variance (ANOVA) and Duncan’s Multiple Range Test (DMRT). The ratio of Nipah fruit pulp to beetroot pulp significantly influenced water content, ash content, pH content, crude fiber content, antioxidant activity, sensory tests on color, taste, aroma, and texture, and overall assessment. In this study, the best treatment for fruit leather was Nipah fruit pulp and beetroot pulp (85:15), with moisture content 7.63%, ash 0.78%, pH 4.40, crude fiber 2.62%, antioxidant activity 118.31 ppm, red color (score 2.00), and sweet taste (score 2.00). Its aroma was slightly fragrant with Nipah fruit and beetroot (score 3.00), its texture was chewy (score 4.43), and the panelists favored the overall rating (score 4.43).